45.6k views
1 vote
Which expression is equivalent to (x Superscript four-thirds Baseline x Superscript two-thirds Baseline) Superscript one-third?

x Superscript two-ninths
x Superscript two-thirds
x Superscript eight-ninths
x Superscript seven-thirds

User ThijsW
by
5.7k points

2 Answers

4 votes

Answer: x 2/3 on edge :)

Explanation:

User Steven Carlson
by
5.4k points
4 votes

Answer:

x Superscript two-thirds

Explanation:


\displaystyle (x^{(4)/(3)}x^{(2)/(3)})^{(1)/(3)}=(x^{(4)/(3)+(2)/(3)})^(1)/(3)=(x^2)^{(1)/(3)}\\\\=x^{(2)/(3)}

_____

The applicable rules of exponents are ...

(a^b)(a^c) = a^(b+c)

(a^b)^c = a^(bc)

User Dubraven
by
4.9k points